The effects of preclinical vascular and autonomous reactivity disturbances on physical workability in young men with atherosclerotic risk factors - V. N. Kim; R. S. Karpov; G. B. Krivulina; V. M. Shevelev (Российский кардиологический журнал, 2007)
Physical efficiency was studied in 142 male students with risk factors of atherosclerosis who had endothelial dysfunction and disturbed vegetative reactivity. High values of rate - pressure product at rest and low level of physical efficiency were found in these subjects. All that indirectly testified to the decrease in oxygen transporting, "recipient" and maximum aerobic resources in young men with risk factors of atherosclerosis and endothelial dysfunction. Relationship of low physical efficiency with endothelial dysfunction and disturbance in vegetative reactivity was found in this study. Therefore, endothelial dysfunction in students with risk factors of atherosclerosis limits functional reserve of energy formation and physical efficiency indicating low level of somatic health of these subjects.